Seasonal dynamics of the bacterial communities associated with cyanobacterial blooms in the Han River - Kim, Minkyung; Lee, Jaebok; Yang, Dongwoo; Park, Hye Yoon; Park, Woojun (Environmental pollution (1987), 2020)
DNA-based analyses of bacterial communities were performed to identify the bacteria co-occurring with cyanobacterial blooms in samples collected at a single site over 2 years. Microcystis aeruginosa was the most predominant species (81% in 2018, and 94% in 2019) within the phylum Cyanobacteria, and microcystins were detected during all cyanobacterial blooms. The stereo microscope and scanning electron microscope observations showed bacterial associations on and around the aggregated M. aeruginosa cells. Culture-independent analyses of filtered bacterial communities showed that the Flavobacterium species in phylum Bacteroidetes (19%) was dominant in the cyanobacterial phycosphere, followed by the Limnohabitans species in Betaproteobacteria (11%). Using principal component analysis, major bacterial genus, including Microcystis and Flavobacterium species, were clustered during cyanobacterial blooms in both years. To identify key bacterial species that develop long-term symbiosis with M. aeruginosa, another culture-independent analysis was performed after the environmental sample had been serially subcultured for 1 year. Interestingly, Brevundimonas (14%) was the most dominant species, followed by Porphyrobacter (7%) and Rhodobacter (3.5%) within the Alphaproteobacteria. Screening of 100 colonies from cyanobacterial bloom samples revealed that the majority of culturable bacteria belonged to Gammaproteobacteria (28%) and Betaproteobacteria (57%), including Pseudomonas, Curvibacter, and Paucibacter species. Several isolates of Brevundimonas, Curvibacter, and Pseudomonas species could promote the growth of axenic M. aeruginosa PCC7806. The sensitivity of M. aeruginosa PCC7806 cells to different environmental conditions was monitored in bacteria-free pristine freshwater, indicating that nitrogen addition promotes the growth of M. aeruginosa. The bacterial communities were performed to identify the bacteria co-occurring with cyanobacterial blooms in samples collected at a single site over 2 years. Flavobacterium species in phylum Bacteroidetes was dominant in the cyanobacterial phycosphere in our culture-independent analysis and Brevundimonas was the most dominant species in the 1-year subcultured sample. Several isolates of Brevundimonas, Pseudomonas, and Curvibacter species could encourage the growth of M. aeruginosa. The sensitivity of M. aeruginosa PCC7806 cells to different environmental conditions was monitored in bacteria-free pristine freshwater, indicating that nitrogen addition promotes the growth of M. aeruginosa. [Display omitted] •Culture-independent analyses in cyanobacterial blooms were performed for 2 years.•Microcystis, Flavobacterium, and Pseudomonas were the major genus.•Brevundimonas was the predominant genus in subcultured cyanobacterial samples.•Brevundimonas species could promote the growth of M. aeruginosa.•Nitrogen addition was the most positive effect on the growth of M. aeruginosa.